2010
DOI: 10.1111/j.1439-0434.2009.01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cereal Luteoviruses and Molecular Diversity of BYDV-PAV Isolates in Central and Southern Iran: Proposal of a New Species in the GenusLuteovirus

Abstract: During a survey, 148 wheat, 70 barley and 24 wild grass samples of plants showing symptoms of yellowing or reddening of leaves and general stunting were collected in central and southern provinces of Iran and tested for Barley yellow dwarf virus (BYDV) and Cereal yellow dwarf virus (CYDV) infection by enzymelinked immunosorbent assay (ELISA) and tissue print immunoassay (TPIA). The results showed the presence of the viruses in most regions. Positive reactions to BYDV-PAV, BYDV-MAV, CYDV-RPV and BYDV-SGV antise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Association of BYDVs with such diseases has been reported previously in Iran showing that these viruses are distributed in all cereal growing provinces of the country (Rastgou et al 2005: Pakdel et al 2010. The molecular analyses conducted in the present study indicated that the distribution of WDV in Iran is also very wide, covering major cereal growing regions of the country.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Association of BYDVs with such diseases has been reported previously in Iran showing that these viruses are distributed in all cereal growing provinces of the country (Rastgou et al 2005: Pakdel et al 2010. The molecular analyses conducted in the present study indicated that the distribution of WDV in Iran is also very wide, covering major cereal growing regions of the country.…”
Section: Discussionsupporting
confidence: 45%
“…Association of BYDVs with these diseases is well established (Rastgou et al 2005: Pakdel et al 2010. However, there have been many yellows cases in which no BYDVs have been identified and it has been suggested that other viruses may also be involved in the cereal yellows disease complex in this country.…”
Section: Introductionmentioning
confidence: 95%
“…It is believed that different virus species dominate in different regions, for example in mainland Europe, the United States, China, Algeria and Iran BYDV‐PAV is thought to be the most abundant species infecting cereals and is therefore considered to be the most agriculturally important (Adhikari et al., 2020; Boubetra et al., 2023; Liu et al., 2019; Pakdel et al., 2010), whereas in the United Kingdom BYDV‐MAV and BYDV‐PAV occur at similar levels (Foster et al., 2004) and in Ireland BYDV‐MAV is the dominant species (Kennedy & Connery, 2005). However, most monitoring surveys were only conducted over a relatively short time‐period (up to three growing seasons) and more up‐to‐date information for some regions is lacking.…”
Section: Yellow Dwarf Virus and Yellow Dwarf Disease: A Brief Introdu...mentioning
confidence: 99%
“…B/CYDVs are the most common group of viruses in Poaceae family plants studied extensively in many continents and countries on a global scale. The presence of these viruses have been reported in some countries like Brazil (Parizoto et al, 2013), Australia (Nancarrow et al, 2014), Pakistan (Siddiqui et al, 2011), Iraq (El-Muadhidi et al, 2001, Tunisia (Hamdi et al, 2020), İran (Rastgou et al, 2005), Hungary (Áy et al, 2008), England/UK (Kendall et al, 1996), China (Tao et al, 2012), Southern Iran (Pakdel et al, 2010), Latvia (Bisnieks et al 2004), Turkey (Usta et al, 2020;Hassan et al, 2018;Ilbagi et al, 2019), Chech Republic and Sweden (Pokorny, 2006), andBulgaria (Bakardjeiva et al, 2006).…”
Section: Introductionmentioning
confidence: 94%